Characterization and Stabilization of the Extract from Mango Seed Kernel in a Cosmetic Emulsion - Pitchaon Maisuthisakul; Thepkunya Harnsilawat (Agriculture and Natural Resources, 2011)
The aim of this study was to systematically investigate the antiradical capacity using 2,2-diphenyl-1-picrylhydrazyl radical scavenging assays, chelating activity and tyrosinase inhibitory activity (including solubility) of mango (Mangifera indica cultivar Chok-Anan) seed kernel extract compared to methyl gallate (MG). The mango seed kernel extract (MSKE) showed significantly (P < 0.05) higher antiradical capacity and tyrosinase inhibitory activity than that of MG. The extract showed higher solubility in glycerol than water. The emulsion-stabilizing properties of MSKE and MG preparations in cosmetic emulsion were investigated using apparent viscosity and total phenolic content. The phenolics affected emulsion stability under high temperature storage and a temperature cycling test. The apparent viscosity increased differently for the emulsion containing the MSKE and MG compared to the base lotion emulsion. The total phenolic content decreased during storage at higher temperature. The results showed that the interaction between the phenolics and the emulsifier, and the inclusion of other ingredients, in emulsion systems are important for cosmetic emulsion stabilization.